Consumers' attitudes toward mobile advertising : a rhetorical approach - Andersson, Sanna (2015)
Mobile advertising adoption has not been as rapid as it could have been, even though the techniques for its full exploitation have existed for years. Understanding consumers’ attitudes toward the phenomenon is crucial in order to enhance the situation. The purpose of this research was to examine young consumers’ perceptions about mobile advertising in order to clarify what type of meanings they give to the phenomenon, what kind of argumentation means are found and in which contexts it is evaluated positive or negative. The theoretical framework of this research is based on the principals of rhetorical social psychology (Billig 1987/1996). The data of this study was gathered by using the method of qualitative attitude approach. The target group was asked to comment the claims presented to them. Eighteen personal interviews were conducted for both Finnish (9) and American (9) young adults. The interviewees’ views and arguments behind the views were categorized and analyzed. Based on the analyses, an interpretation of their attitudes and the way the attitudes appeared in the interviewees’ speech could be done. Nine argumentation categories could be formed. Further, four contextual dimensions, from which the argumentation was done could be distinguished: 1. Societal 2. User (including advertiser, consumer and personal role), 3. Technical, and 4. Time dimension. Attitudes and objects of attitudes varied in different dimensions. Mobile advertising was experienced more positively in the role of a member of society than in the role of a customer. The biggest concerns were the purposes the advertiser uses one’s information and the fear of one’s information getting into wrong hands. From advertiser’s perspective mobile advertising was seen only positive. Mobile advertising was viewed more positively from the general consumer view than from the role of the receiver/oneself. Mobile advertising was perceived safe and reliable in general, but the functionality of personalized advertising caused doubts. Mobile advertising was seen better and more beneficial in the future, when it will be more developed. Certain parts of the results show similarities to previous research.